Cluster headache: When to worry? Two case reports. (April 2017) - Bellamio, Matteo; Anglani, Mariagiulia; Mainardi, Federico; Zanchin, Giorgio; Maggioni, Ferdinando
Background: The clinical criteria for cluster headache (CH) are included in Chapter 3 of the International Classification of Headache Disorders, 3rd beta edition (ICHD-III). CH may sometimes be secondary to other pathologies. Case reports: We report two patients in whom the clinical features of CH initially fulfilled the ICHD-III criteria, but who later presented some radical modifications in headache natural history as a result of a secondary pathology. The first case of CH was secondary to a pontine cavernous angioma and the second to a cerebral venous thrombosis. Conclusion: We highlight the importance of clinical modifications of CH that could suggest clinical investigations should be performed or repeated to exclude a secondary pathology in a previously diagnosed cluster headache. Some of the pathological mechanisms of CH and brain lesions are discussed.